2006
DOI: 10.1016/j.biocontrol.2005.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Lygus lineolaris (Hemiptera: Miridae) and Frankliniella occidentalis (Thysanoptera: Thripidae) by Bombus impatiens (Hymenoptera: Apidae) vectored Beauveria bassiana in greenhouse sweet pepper

Abstract: The ability of bumble bees to disseminate conidia of Beauveria bassiana (Balsamo) Vuillemin from hive-mounted dispensers to greenhouse sweet peppers for the control of tarnished plant bug (TPB) and western Xower thrips (WFT) was investigated in greenhouse trials using large screened enclosures. Samples collected from the enclosures (four treatments) on two sampling dates showed that 97, 90, 91, and 42% of the collected bees, Xowers, leaves, and TPB, respectively, showed detectable densities of B. bassiana on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…As a consequence, the conidia of the fungus B. bassiana GHA are able to survive and grow on the bumblebee body, resulting in death of the insect. In contrast, Al‐Mazra'awi et al 20 reported that B. bassiana GHA is safe for use in combination with the Eastern North American bumblebee, B. impatiens , in a vector system to control pest insects; however, it should be mentioned that in the latter experiments the fungus B. bassiana was applied as a dry formulation. In the same year, Al‐Mazra'awi et al 36 made a similar report that honey bees were not affected when exposed to dormant conidia via walking through a dry powder formulation of B. bassiana conidia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As a consequence, the conidia of the fungus B. bassiana GHA are able to survive and grow on the bumblebee body, resulting in death of the insect. In contrast, Al‐Mazra'awi et al 20 reported that B. bassiana GHA is safe for use in combination with the Eastern North American bumblebee, B. impatiens , in a vector system to control pest insects; however, it should be mentioned that in the latter experiments the fungus B. bassiana was applied as a dry formulation. In the same year, Al‐Mazra'awi et al 36 made a similar report that honey bees were not affected when exposed to dormant conidia via walking through a dry powder formulation of B. bassiana conidia.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, in the present tests the bumblebees were treated via contact with a water suspension of the conidia, and this may explain the high worker toxicity observed. Al‐mazra'awi et al 20 and Fernandes et al 31 also reported negative side effects on B. impatiens and A. mellifera when the surfactant Tween 80 was added to Botanigard ® , leading to good germination. In this context, the present authors believe that the toxicity of the fungus B. bassiana may differ owing to differences in conidial thermotolerance and the type of formulation and exposure method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, entomopathogenic microorganisms provide an alternative method to reduce the use of synthetic pesticide in integrated pest management in sustainable agriculture (Liu et al, 2002;Al-mazaawi et al, 2006 (Vanitha and Parthasarathy, 2017) has been used extensively for the control of wide range of insect pests and also induce systemic resistance by activating lipoxygenase pathways. It is also known to be a plant growth promoting fungi (PGPF), when applied as consortial mode into soil.…”
Section: Issn: 2319-7706 Volume 6 Number 11 (2017) Pp 3300-3313mentioning
confidence: 99%
“…in areas used to rear silkworm (Bombyx mori Steinhaus) with no adverse effect . In fact, Butt et al (1998) used honeybees to vector M. anisopliae for the control of the pollen beetle, Meligethes aeneus Fabricius, while the bumble bee, Bombus impatiens Cresson, has successfully vectored B. bassiana (Al-Mazra'awi et al 2006). Utilizing isolates with a broad ecological host range is not without merit.…”
Section: Host Specificity Of Isolatementioning
confidence: 99%